Competition policy, trade and the global economy: Existing WTO elements, commitments in regional trade agreements, current challenges and issues for reflection - Robert D. Anderson; William E. Kovacic; Anna Caroline Müller; Nadezhda Sporysheva (World Trade Organization (WTO), 2018)
Competition policy, today, is an essential element of the legal and institutional framework for the global economy. Whereas decades ago, anti-competitive practices tended to be viewed mainly as a domestic phenomenon, most facets of competition law enforcement now have an important international dimension. Examples include: the investigation and prosecution of price fixing and market sharing arrangements that often spill across national borders and, in important instances, encircle the globe; multiple recent, prominent cases of abuses of a dominant position in high-tech network industries; important current cases involving transnational energy markets; and major corporate mergers that often need to be simultaneously reviewed by multiple jurisdictions. Beyond competition law enforcement per se, increasingly, major issues of competition policy (e.g., the impact on competition of the structure and scope of intellectual property rights or the role of state-owned enterprises) implicate the interests of multiple jurisdictions. [...]
Keywords: F02; F13; F23; F53; L40; L44; L49; N40; 330; competition policy; anti-competitive practices; international trade policy; WTO agreements; regional trade agreements; state-owned enterprises; competitive neutrality; the digital economy